Peningkatan Pengetahuan Dan Pencegahan Penyakit ISPA Pada Siswa-Siswi Smpn 6 Bengkulu Tengah - Nopia Wati; Agus Ramon; Hasan Husin; Emi Kosvianti (Gayaku Publisher, 2022)
Acute Respiratory Tract Infection (ARI) is a major cause of infectious disease morbidity and mortality in the world. One of the causes of the high incidence of ARI is due to lack of knowledge about ARI. One thing that can be done to increase knowledge is to provide health education about ARI. This community service aims to provide education about ARI disease during the pandemic at SMPN 6 Bengkulu Tengah. This activity was attended by 20 students using LCD projectors and leaflets. The method used is lectures and discussions as well as pre-test and post-test. The results of the pre-test of students' knowledge of ARI with the most lack of knowledge were 8 people (40.0%) while after being given education in the form of health counseling, the increase in participants' knowledge became a sufficient level of 10 people (50.0%). Hopefully the results of this research can be useful for students.